Payment Choice in International Trade: Theory and Evidence from Cross-country Firm Level Data - Andreas Hoefele; Tim Schmidt-Eisenlohr; Zhihong Yu (Center for Economic Studies and ifo Institute (CESifo), 2013)
When trading, firms choose between different payment contracts. As shown theoretically in Schmidt-Eisenlohr (forthcoming), this allows firms in international trade to optimally trade-off differences in financing costs and enforcement across countries. This paper provides evidence from a large number of countries that shows that country characteristics are indeed central determinants of the payment contract choice. As predicted, the use of open account decreases in financing costs and contract enforcement in the source country. We extend the theory and test two additional predictions. First, we show that the more complex the industry of a firm, the more important is the quality of contract enforcement and the less important are the financing costs for the contract choice. Second, we compare direct and indirect exporters and find evidence that suggests that intermediaries play a relevant role in contract enforcement across borders.
Keywords: F12; F30; G21; G32; 330; trade finance; payment contracts; industry complexity; developing countries; trade intermediation